OP35 Endoscopic and deep remission at 1 year prevents disease progression in early Crohn's disease: long-term data from CALM. (25th January 2019) - Yzet, C; Ungaro, R; Bossuyt, P; Baert, F; Vanasek, T; D'Haens, G; Joustra, V; Panaccione, R; Novacek, G; Armuzzi, A; Golovchenko, O; Prymak, O; et al.
Abstract: Background: We aimed to describe the long-term impact of achieving endoscopic and deep remission among participants in the effect of tight control management on CD (CALM) trial. Methods: We analysed medical records from patients with follow-up data since end of CALM. Patients were stratified by outcomes in CALM at 1 year: clinical remission (Crohn's disease activity index, CDAI <150), endoscopic remission (Crohn's disease endoscopic index of severity, CDEIS <4 with no deep ulcerations), and deep remission (CDAI <150, CDEIS <4 with no deep ulcerations, and no steroids for ≥8 weeks). The primary outcome was a composite of major adverse outcomes reflecting CD progression: new internal fistula/abscess, stricture, perianal fistula/abscess, CD hospitalisation, or CD surgery since end of CALM. Kaplan–Meier and Cox regression methods were used to compare composite rates between patients who achieved or did not achieve remission at 1 year. Adjusted hazard ratios (aHR) with 95% confidence intervals (CI) are reported, controlling for randomisation arm and baseline variables significant at p < 0.2 level. Results: One hundred twenty-two patients with median age 29 years (IQR 22.5–37) and median disease duration 0.2 years (IQR 0.1–0.8) were included. Median follow-up time from end of CALM was 3.02 years (range 0.05–6.26 years). Fifty per cent were randomised to the tight control arm. There were no significant differences in baseline characteristics in patients with follow-up data and those lost to follow-up with the exception of a slightly higher CDEIS score in patients lost to follow-up (14.6 vs. 12.9, p = 0.04). Thirty-four patients (27.9%) had a major adverse outcome during follow-up. Patients in clinical remission at 1 year did not have significantly lower rates of the composite endpoint (log-rank p = 0.15). Patients in endoscopic and deep remission at the end of CALM were significantly less likely to have a major adverse event over time (Figures 1 and 2). After adjusting for age, disease duration, prior surgery, prior stricture, and randomisation arm, endoscopic remission (aHR 0.44, 95% CI 0.20–0.96, p = 0.038) and deep remission (aHR 0.25, 95% CI 0.09–0.72, p = 0.01) were significantly associated with lower risk of major adverse events. Conclusions: Early CD patients who achieve endoscopic or deep remission after 1 year of intensive treatment are less likely to have disease progression over a median of 3 years.